BtaE, an adhesin that belongs to the trimeric autotransporter family, is required for full virulence and defines a specific adhesive pole of Brucella suis. - Ruiz, Veronica (2013)
Brucella is responsible for brucellosis, one of the most common zoonoses worldwide that causes important economic losses in several countries. Increasing evidence indicates that adhesion of Brucella spp. to host cells is an important step to establish infection. We have previously shown that the BmaC unipolar monomeric autotransporter mediates the binding of Brucella suis to host cells through cell-associated fibronectin. Our genome analysis shows that the B. suis genome encodes several additional potential adhesins. In this work, we characterized a predicted trimeric autotransporter that we named BtaE. By expressing btaE in a nonadherent Escherichia coli strain and by phenotypic characterization of a B. suis ΔbtaE mutant, we showed that BtaE is involved in the binding of B. suis to hyaluronic acid. The B. suis ΔbtaE mutant exhibited a reduction in the adhesion to HeLa and A549 epithelial cells compared with the wild-type strain, and it was outcompeted by the wild-type strain in the binding to HeLa cells. The knockout btaE mutant showed an attenuated phenotype in the mouse model, indicating that BtaE is required for full virulence. BtaE was immunodetected on the bacterial surface at one cell pole. Using old and new pole markers, we observed that both the BmaC and BtaE adhesins are consistently associated with the new cell pole, suggesting that, in Brucella, the new pole is functionally differentiated for adhesion. This is consistent with the inherent polarization of this bacterium, and its role in the invasion process.